2021
DOI: 10.1037/tra0000921
|View full text |Cite
|
Sign up to set email alerts
|

Moral injury and ICD-11 complex PTSD (CPTSD) symptoms among treatment-seeking veterans in the United Kingdom.

Abstract: Military veterans often encounter events with chronic or repeated traumas of an interpersonal nature that might lead to emotional, relational, and spiritual suffering. Research is needed to assess whether and/or how emerging conceptions of moral injury (MI) align with existing trauma-related conditions. Focusing on 173 veterans from the United Kingdom who had recently pursued mental health treatment, we examined associations between self-and other-directed outcomes related to MI and World Health Organization I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 8 publications
1
20
1
Order By: Relevance
“…Moreover, profound changes in cognitions and world assumptions (e.g., "I am a rotten person"), and dysfunctional strategies such as self-destruction, aimed to relieve moral pain, may possibly follow. Importantly, if left unresolved, these PMIEs might result in deep psychiatric and functionally aversive consequences, such as posttraumatic stress disorder (PTSD; Koenig et al, 2019) and complex PTSD (CPTSD; Currier et al, 2021).…”
Section: Moral Injurymentioning
confidence: 99%
“…Moreover, profound changes in cognitions and world assumptions (e.g., "I am a rotten person"), and dysfunctional strategies such as self-destruction, aimed to relieve moral pain, may possibly follow. Importantly, if left unresolved, these PMIEs might result in deep psychiatric and functionally aversive consequences, such as posttraumatic stress disorder (PTSD; Koenig et al, 2019) and complex PTSD (CPTSD; Currier et al, 2021).…”
Section: Moral Injurymentioning
confidence: 99%
“…PTSD is known to be comorbid with common psychopathologies (Currier, Foster, Karatzias, & Murphy, 2021 ) and the emerging body of literature suggests that CPTSD shares this characteristic, potentially to a greater degree (Armour, 2015 ). Individuals with CPTSD are more likely to report experiencing higher levels of anxiety and depression (Karatzias et al, 2019 ; Mur-Crepulja et al, 2020 ; Murphy, Karatzias, Busuttil, Greenberg, & Shevlin, 2021 ), suicidality (Hyland, Shevlin, Fyvie, & Karatzias, 2018 ; Karatzias et al, 2019 ), moral injury (Mur-Crepulja et al, 2020 ; Murphy et al, 2021 ), substance misuse and psychosis (Facer-Irwin, Karatzias, Bird, Blackwood, & MacManus, 2021 ), and alcohol misuse (Hitch, Toner, & Armour, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We identified four classes of patients: a MI class ( n = 192; 11.27%), a MI-PTSD class ( n = 565; 33.18%), a PTSD class ( n = 644; 37.82%), and a Neither MI-nor PTSD class ( n = 302; 17.73%). The identification of classes characterized by high MI reflects findings of three latent profile analyses (LPA) of MI in military veterans ( 43 45 ). These previous studies identified two groups that were, respectively, high and low in MI plus complex PTSD ( 43 ), two MI groups characterized by psychological distress and spiritual distress, respectively, as well as a non-distressed group ( 44 ), and a high symptoms group, lower symptoms group, and potential MI group ( 45 ).…”
Section: Discussionmentioning
confidence: 59%
“…The identification of classes characterized by high MI reflects findings of three latent profile analyses (LPA) of MI in military veterans (43)(44)(45). These previous studies identified two groups that were, respectively, high and low in MI plus complex PTSD (43), two MI groups characterized by psychological distress and spiritual distress, respectively, as well as a non-distressed group (44), and a high symptoms group, lower symptoms group, and potential MI group (45). Altogether these results confirm that MI is a prominent form of symptomatology amongst police officers and veterans exposed to profession-related trauma.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation